Redescription of the Deep-Sea Cirrate Octopod Cirroteuthis magna Hoyle, 1885, and Considerations on the Genus Cirroteuthis (Mollusca: Cephalopoda) - Guerra, Ángel; Villanueva, Roger; Nesis, Kir N.; Bedoya, J. (Rosenstiel School of Marine and Atmospheric Science, 1998)
31 pages, 29 figures, 4 tables, 1 appendix. The deep-living octopod Cirroteuthis magna Hoyle, 1885 is redescribed, based on the only three specimens known of the species: a mature female (holotype) captured in the south Indian Ocean between Prince Edward and Crozet islands at 2557 m and two specimens, one submature female and one mature male, recently captured in the central Atlantic at 1300 and 3351 m depth, respectively. Video images from the capture of the latter specimen were recorded. This species is characterized by its very great size (to 1300 mm TL), making it the largest known cirrate octopod; butterfly-like shell with open wings; very voluminous eyes with large lenses; arm length 73-79% of the total length; primary web inserted at different levels on the dorsal and ventral ends of the dorso- and ventrolateral arms on both sides, and at the same level on both ends of the dorsal and ventral arms; each arm is independent of the primary web, and is connected with it by a single vertical membrane or intermediate web that is attached along the dorsum of the arm; absence of nodule at the fusion point of both webs. Very large cirri, the first cirri commencing between the 4th and 5th suckers, with three types of suckers on all the arms; cylindro-conical form and those with the acetabulum highly deformable on the first 2/3 of arms and barrel-like on the rest of the arm; absence of particularly enlarged suckers. C. magna is compared with C. muelleri and other related species. Sperm sacs and spermatozoids from C. magna and C. muelleri are described and compared. The Cirroteuthis genus is reviewed and a diagnosis is proposed. This study confirms that the members of the Cirroteuthidae family show several unusual features of great interest. During this study one of the authors (R.V.) was supported by a post-doctoral fellowship from the Spanish Ministery of Education and Science. Peer reviewed